Analysis of Physical Education Students' Learning Obstacles in basic Research Course - Yahya Eko Nopiyanto; Yarmani; Tono Sugihartono; Arwin Arwin; Syafrial Syafrial; Ari Sutisyana; Dian Pujianto; Andika Prabowo; Ipa Sari Kardi; Ibrahim Ibrahim; Cahyo Wibowo; Arief Ibnu Haryanto; Rasyono Rasyono (UNIB Press, 2024)
Obstacles in the learning process need to be an important concern for every lecturer in charge of the subject. Therefore, the purpose of this research is to reveal the learning barriers of physical education students in attending basic research lectures. The qualitative descriptive method is implemented to achieve research objectives. A total of 43 physical education students were involved in this study as subjects who provided the required information. Instruments consisting of observation, documentation, and semi-structured interviews are used to collect the required data. Analysis of the collected data using data triangulation. The results of the study stated that students experienced obstacles in attending basic research lectures, especially in the section on compiling research backgrounds and conducting research data analysis.